Predictors of gestational diabetes mellitus among first-trimester pregnant women: Evidence from a health center in West Java, Indonesia - Noviyanti; Dede Waslia; Intan Nafisah (Majalah Obstetri & Ginekologi, 2026)
HIGHLIGHTS This study identifies body mass index (BMI) and family history of diabetes as significant determinants of gestational diabetes mellitus (GDM) among first-trimester pregnant women. The findings emphasize the need for early screening and preventive interventions in primary health care to reduce GDM risk and its associated complications. ABSTRACT Objective: Many first-trimester pregnant women at a health center in West Java, Indonesia, have been reported to exhibit elevated blood glucose levels and excessive BMI, while documentation of family history of diabetes remains inadequate. Local studies examining the relationship between these factors and gestational diabetes mellitus (GDM) are still limited. This study aimed to determine the association between maternal age, BMI, and family history of diabetes and the incidence of GDM in first-trimester pregnant women. Materials and Methods: This case–control study involved 96 first-trimester pregnant women attending antenatal care at the Health Center with Inpatient Care in Cikalong Wetan, Bandung, Indonesia, in 2024, who were selected through purposive sampling. Participants were divided into cases (n = 48), defined by glucose levels =140 mg/dL, and controls (n = 48) with glucose levels